How Much Do Psychological Factors Affect Lack of Return to Play After Anterior Cruciate Ligament Reconstruction? A Systematic Review. Issue 5 (20th May 2019) - Nwachukwu, Benedict U.; Adjei, Joshua; Rauck, Ryan C.; Chahla, Jorge; Okoroha, Kelechi R.; Verma, Nikhil N.; Allen, Answorth A.; Williams, Riley J.
Background: Variables affecting return to sport after anterior cruciate ligament reconstruction (ACLR) are multifactorial. The nonphysical factors germane to successful return to play (RTP) are being increasingly recognized. Purpose: To (1) evaluate the available evidence base for psychological factors relating to RTP after ACLR, (2) identify psychological factors affecting RTP after ACLR, and (3) understand currently available metrics used to assess psychological RTP readiness. Study Design: Systematic review; Level of evidence, 4. Methods: A review of the MEDLINE database was performed for studies reporting RTP after ACLR. Studies reporting on the psychological determinants of RTP were included. Demographic, methodological, and psychometric properties of the included studies were extracted. Weighted analysis was performed after patients were pooled across included studies. Results: Of 999 studies identified in the initial search, 28 (2.8%) studies, comprising 2918 patients, were included; 19 studies (n = 2175 patients) reported RTP rates. The mean time for RTP was 17.2 months. There was a 63.4% rate of RTP, and 36.6% of patients returning to sport were not able to perform at their prior level of play. Of the 795 patients who did not achieve RTP, 514 (64.7%) cited a psychological reason for not returning. Fear of reinjury was the most common reason (n = 394; 76.7%); other psychological factors included lack of confidence in the treated knee (n = 76; 14.8%), depression (n = 29; 5.6%), and lack of interest/motivation (n = 13; 2.5%). The Tampa Scale for Kinesiophobia, the Hospital Anxiety and Depression Scale, the ACL–Return to Sport after Injury scale, and the Knee Self-Efficacy Scale were reported measures for assessing the influence of psychology on RTP. Conclusion: Psychological factors play an important role in RTP after ACLR. Among studies evaluating the impact of psychology on RTP, there was a delay in returning as well as lower RTP rates compared with the previously reported normative literature. Fear of reinjury was the most commonly reported impediment to RTP. The psychosocial measures identified in this review may have a role in RTP protocols for assessing mental resiliency; however, their roles need to be further investigated and validated in patients who have undergone ACLR.